Collecting Coins and Medals in 18th-Century Sweden - Haidenthaller, Ylva (Artium Quaestiones, 2023)
During the 18th century, collections of coins and medals were familiar sights. The collectors ranged from scholars to amateurs, men and women and the collectables tempted collectors for various reasons: they signified wealth and knowledge, they rendered historical events or current politics in material form, or they were miniature artworks and financial investments. Also, the visual and material culture that involved collecting coins and medals consisted of cabinets and numismatic publications. But how were numismatic collections amassed, and how were they used? What did it mean to own a coin and medal collection? This article discusses the practices of collecting numismatics in 18th-century Sweden through various case studies concerning private and public collections, such as the Uppsala University coin cabinet or the possessions of politician Carl Didric Ehrenpreus, numismatist Elias Brenner, medal artist Arvid Karlsteen, and merchant-wife Anna Johanna Grill. These cases illuminate the diverse motivations behind collecting, from intellectual curiosity to social status. These case studies include immaterial facets such as witty discussions and international networks and material aspects such as coins, medals, cabinets, letters, and publications. Based on contemporary written sources, this article sheds light on how numismatic objects were bought, sold and circulated, highlighting the market dynamics of collecting. Furthermore, the examples examine how numismatic publications were used next to the objects, contributing to hermeneutic study and the collecting process. The written records provide insight into the scholarly discourse surrounding these collections, offering a glimpse into the intellectual context of the time. Finally, the article will add to the understanding of values and ideas attached to the practices of collecting coins and medals in early modern Europe. It elucidates the role of numismatics as a collecting practice, as well as how it shaped cultural perceptions, underscoring the intricate interplay between material and visual culture, society, and the production of knowledge during this period.